Applying liquid chromatography-tandem mass spectrometry to assess endodontic sealer microleakage - André Luiz da Costa MICHELOTTO; João Cleverson GASPARETTO; Francinete Ramos CAMPOS; Gilson Blitzkow SYDNEY; Roberto PONTAROLO (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The objective of this study was to describe a new method for the quantitative analysis of a microleakage of endodontic filling materials. Forty extracted single-rooted teeth were randomly divided into three experimental groups. After root canal shaping, the experimental groups were filled using the lateral condensation technique with the Epiphany system (G1), with gutta-percha + Sealapex (G2), and with gutta-percha + AH Plus (G3). Each root was mounted on a modified leakage testing device, and caffeine solution was used as a tracer (2000 ng mL-1, pH 6.0), applied in the coronal direction towards the tooth apex, creating a hydrostatic pressure of 2.55 kPa. Presence of caffeine in the receiving solution was measured after 10, 30, and 60 days, using high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). None of the groups presented microleakage at 10 days. At 30 days, G2 and G3 showed similar infiltration patterns (means: 16.0 and 13.9 ng mL-1, respectively), whereas G1 showed significantly higher values (mean: 105.2 ng mL-1). At 60 days, leakage values were 182.6 ng mL-1for G1, 139.0 ng mL-1 for G2, and 53.5 ng mL-1 for G3. AH Plus showed the best sealing ability and HPLC-MS/MS showed high sensitivity and specificity for tracer quantification.